2012
DOI: 10.1111/j.1464-5491.2012.03606.x
|View full text |Cite
|
Sign up to set email alerts
|

Which aspects of executive dysfunction influence ability to manage diabetes in older adults?

Abstract: On the one hand, in older adults, executive dysfunction detected by objective tests is associated with poor glycaemic control and may be considered before prescribing complex treatment regimens. On the other hand, self-reported executive dysfunction is associated with risk and fear of falls, and more affective symptoms, which may indicate higher awareness of subtle deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 27 publications
4
24
0
3
Order By: Relevance
“…The association with education is in good agreement with other studies as increasing age and fewer years of education are known to affect the TMT results due to the types of tasks given (Munshi et al 2012;Voos et al 2011;Tombaugh 2004).…”
Section: Discussionsupporting
confidence: 87%
“…The association with education is in good agreement with other studies as increasing age and fewer years of education are known to affect the TMT results due to the types of tasks given (Munshi et al 2012;Voos et al 2011;Tombaugh 2004).…”
Section: Discussionsupporting
confidence: 87%
“…A recent meta-analysis identified reliable decrements associated with T2DM that were relatively uniform across EF measurement approaches and conceptual subtypes of EF (8) Impaired EF among the T2DM population is potentially problematic because of the role of EF integrity in the consistent implementation, assessment and adaptation behaviours necessary in diabetes self-care (20)(21)(22)(23)(24). For example, EF has been implicated in the ability to perform healthy dietary behaviours, consistently follow physical activity recommendations, adhere to medication regimens and maintain weight loss (21,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), all of which are required for effective management of T2DM (37). For this reason, effective disease management may rely partially on intact executive control capacities.…”
Section: Resultsmentioning
confidence: 99%
“…However, some executive functions could be important for perform complex tasks required for self care, such as blood glucose monitoring and, dietary modification and regular physical activity. One study revealed that in older adults, executive dysfunction detected by objective tests is associated with poor glycaemic control [38]. Impairments in executive function are associated with poor adherence to medication, low independence or instrumental activities of daily living, and low autonomy and inability to make decisions.…”
Section: Discussionmentioning
confidence: 99%